Determination of tool wear drilling process of aluminum 6061 and brass C3604 by using CNC robodrill machine - Hadi, Abdul Salaam; M. A. N., Mu’tasim (Institute of Physics Publishing, 2024)
Hole making process is a stimulating process as it impacts the drilling tool's performance and wear. The main objective of this paper is to determine the drilling tool wear by using step-by-step drilling approaches used by most of the manufacturing companies. Two types of materials involved; Aluminum 6061 & Brass C3604. Firstly, the raw material grade was confirmed by testing it using an Oxford Spectrometer. Four types of drilling tools are used; center drill diameter 3.00 mm; drill diameter 10.00, 13.00 and 14.50 mm. The drilling tool material used is High-Speed Steel (HSS). The cutting parameter used is stated in detail in the methodology section. Two approach are used to determine the tool life; measuring the holes diameter produced by using Vernier caliper; graphical form with the help of the camera. The major finding of this research is the understanding on how the cutting process react with the drilling tool during the cutting process as discussed in the results and discussions. The tool life of a center drill, drilling tool diameter 10.00 mm, 13.00 mm and 14.50 mm in drilling Aluminum 6061 is 476, 250, 485 and 499 holes while for Brass C3604 is 360, 190, 360 and 375 holes.